HISTORY OF NOTARY OFFICES IN UZBEKISTAN (1991-2024) - Kanoatov Shahzod Gayratovich (Western European Studies, 2025)
This article describes in detail the significant stages of development of notary offices in Uzbekistan during the period 1991-2024. The system, which was established on the basis of state notary services in the early years of independence, expanded with the introduction of private notaries in the 2000s, Uzbekistan plans to further improve the quality of services for citizens by further digitizing the notary system, adapting it to international standards, and improving the qualifications of notaries, and the fact that the notary system plays an important role in the legal and economic system of Uzbekistan, contributing to the sustainable development of the country, and that it is important to further develop this area
Keywords: Republic of Uzbekistan; notary system; legal system